Pengembangan modul pesawat sederhana berbasis problem based learning untuk meningkatkan pemahaman peserta didik - Ntelok, Zephisius Rudiyanto Eso; Jamun, Yohannes Marryono; Hasni, Maria (Academy of Education Journal, 2024)
This research at SDK Santa Agnes Ruteng IV. This study was intended to develop teaching materials for science subjects on the topic of Simple Machines to Enhance the Understanding of Grade IV Students. The method applied in this research was Research and Development (R & D) utilizing the ADDIE framework. ADDIE stands to Analyse, Design, Development, Implementation, Evaluation, which are stages in the research process. However, due to the time constraints and limitations in the researcher's abilities, the development model in this study was limited to four stages: analysing, design, development, and implementation. The module was developed and structured through a validation process by experts in the fields of content, media, and language. The average validation scores obtained from content experts were 3.46, categorized as valid; media experts scored 3.83, also categorized as valid; and language experts scored 3.50, categorized as valid. Thus, the overall average validation score from the three expert assessments was 3.59, and based on the validity categorization criteria, the teaching module fell into the "Valid" category with a percentage of 83.56%. Normality tests also yielded a value for the experimental class of 0.008 > 0.005, indicating that students' learning interests were normally distributed. Furthermore, the one-sample t-test for students' learning interests resulted in a negative t value, with a calculated t value of -5.594 < the critical t value of 1.970, rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). This implies that there is an influence of using PBL-based modules by fourth-grade students at SDK Santa Agnes Ruteng IV. The implementation fallouts of the learning process showed a very good level of practicality with a percentage of 93.74%. The readability of the teaching module, as evaluated by three teachers, had a readability rate of 92.03%, categorized as good, while the readability by students was 96.56%, also categorized as good. Moreover, the success rate of the developed module achieved an average N-Gain improvement of 0.71, classified as a significant improvement. Based on the research findings, it can be concluded that the module on simple machines using the problem-based learning approach is valid, user-friendly, and effective. Therefore, the developed module is deemed suitable for use as one of the teaching materials in science education for the topic of simple machines.